Surveying principles and methods - Yan, Haowen (Science Press ; Alpha Science International, 2012)
Focuses on measuring and recording the positions and elevations of the points on the Earth surface. This book consists of two parts: conventional surveying and modern surveying. It is an old discipline but it has absorbed fresh nutrition from satellite-based surveying, remote sensing and geographic information science in recent decades.